THE RELATIONSHIP OF KNOWLEDGE AND ATTITUDE ABOUT FEVER AND ITS TREATMENT IN CHILDREN AT SHANTY CLINIC MEDAN - Butar-butar, Maria Haryanti; Sholikhah, Stevany; Napitupulu, Linda Hernike (Tadulako University, 2018)
Background & Objective: Fever is a condition of an increase in body temperature. Fever is a condition of body temperature above 37.5 Â° C. Fever is part of the immune process that is fighting infections caused by viruses, bacteria, or parasites. The aim is to determine the relationship between knowledge and attitudes of mothers about fever with treatment of fever in children at the shanty clinic.Material and Method: The study design used analytical survey research using cross sectional. Technique in this study was accidental sampling, as many as 47 respondents, and analysis data with Chi-Square statistical test. Result: Knowledge distribution with a good majority of 20 people (42.6%), Distribution of attitudes with a positive majority of 18 people (38.2%). The majority of the handling categories were 32 people (68.1%). Poor 12 respondents (37.5%) with the category of handling The results of the study showed a significant relationship between maternal knowledge of fever and treatment of fever in children with p-value = 0.000, attitude categories with handling fever in children related to p-value = 0.001. Conclusion: There is a relationship between knowledge and attitudes about fever with treatment of fever in children at the Shanty Medan Clinic. To increase maternal knowledge about fever by treating fever in children so that the mother is not too worried if her child has a fever. By monitoring the child's body temperature, compressing the child on the forehead, armpits and folds of the thighs and giving the child plenty to drink.